2020
DOI: 10.1016/j.aninu.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of toasting grain silages from field peas (Pisum sativum) and field beans (Vicia faba) on in vitro gas production, methane production, and post-ruminal crude protein content

Abstract: Legume grains such as field peas and field beans can be produced on a local level, and may be reliable sources of dietary protein and energy apart from common soybean and rapeseed meals. In ruminants, protein, starch, and carbohydrates from peas and field beans are fermented in large part before reaching the small intestine. The objective of this study was to evaluate the effects of a combination of ensiling and hydro-thermic treatment (i.e., toasting at 160 °C for 30 min) of grains of peas and field beans on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Furthermore, Kulivand and Kafilzadeh reported that 80% of gas production was achieved within 21 h using the rumen fluid 25 . Li et al 26 reported an optimum methane production of 14.9 mL after around 72 h, and Bachmann et al 27 reported that the optimum gas production for beans samples was at around 16 h. Dagaew et al 28 performed 96 h of biogas production in the AD process and found out that the optimum gas production was achieved at around 24 h.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kulivand and Kafilzadeh reported that 80% of gas production was achieved within 21 h using the rumen fluid 25 . Li et al 26 reported an optimum methane production of 14.9 mL after around 72 h, and Bachmann et al 27 reported that the optimum gas production for beans samples was at around 16 h. Dagaew et al 28 performed 96 h of biogas production in the AD process and found out that the optimum gas production was achieved at around 24 h.…”
Section: Introductionmentioning
confidence: 99%
“…Forages should have less of Part b, but for feeds containing high-value biological proteins, Part b should be increased, so that most of the protein could pass through rumen digestion and be absorbed. Gas production during in vitro incubation indicates ruminal degradation and microbial activity [ 27 ], and a higher b fraction indicates higher rumen undegradable protein (RUP) content [ 28 ]. Yuan and Wan [ 29 ], and Ayaşan et al [ 30 ] reported negative values for Part a, which is consistent with the findings of the current investigation.…”
Section: Resultsmentioning
confidence: 99%
“…However, an excess of heat exposure (time or intensity) might also protect the protein from postrumen compartment digestion [15,16]. Studies have reported the effects of autoclaving [17], toasting [18], microwave heating [19,20], and xylose treatment [21] on the improvement of the RUP content of protein sources. However, there are still contradictory results regarding these methods [5,22].…”
Section: Introductionmentioning
confidence: 99%